Chelovek i zakon . Chelovek i zakon . People and the Law . Человек и закон - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Political crisis in Russia; living and work conditions for inmates; "Newspaper for Prisoners"; accusations of corruption in the Russian armed forces. Contributors: Krauze, IUrii (Anchor) Series description: Socio-political program. Broadcasted since 1974. The program is dedicated to the most important juridical, political, economic, and social issues. The program shows the work of the law enforcement authorities, and does investigative reporting. Политический кризис в России; условия работы и содержания людей в местах лишения свободы; представление "Газеты для зэков"; обвинения в коррупции в вооруженных силах России. Создатели: Краузе, Юрий (Ведущий/Ведущая) Описание серии: Общественно-политическая программа. Выходит с 1974 года. Основная тематика программы — важнейшие события в политической, экономической и социальной жизни страны. Выпуски освещают деятельность правоохранительных органов, включают журналистские расследования и разоблачения.